PENGARUH CUSTOMER RELATIONSHIP MARKETING DAN CORPORATE IMAGE TERHADAP LOYALITAS KONSUMEN - Seleman, Gabriela Ernawati; Maduwinarti, Ayun; Pratiwi, Ni Made Ida (Jurnal Dinamika Administrasi Bisnis, 2015)
This study analyzes of the effect of customer relationship marketing and corporate image to customer loyalty. The object of this study is Bank Jatim in Surabaya. The research problem refers to competition in the banking industry had rapidly gave freedom to customers indetermining the choice to use their services, so if the value received was not as expected then the customers were easy to move to another bank, which was considered in accordance with the customers wishes. So bank must used the strategic who can building customers loyalty. Customer relationship marketing and corporate image was some strategic to make customers loyalty. The research used 100 respondent, and the respondent were client of the Jatim branch in Untag Surabaya. Data was collected using observation dan questionnaires. The results showed that customer relationship Â marketing and corporate image was influence on customer loyalty of bank Jatim.Â Keywords: Customer relationship marketing, corporate image and loyalty